2017
DOI: 10.5539/gjhs.v9n9p158
|View full text |Cite
|
Sign up to set email alerts
|

Perception of the Saudi Community towards Human Papilloma Virus Vaccination in Jeddah, Saudi Arabia

Abstract: To examine the awareness and perception of Saudi community towards Human Papillomavirus Vaccination. A cross-sectional study has examined the perception and awareness of Saudi individuals towards Human Papillomavirus HPV vaccination. A sample of 278 Saudi individuals were included. A close-ended survey questionnaire was employed to collect the data of Papillomavirus HPV vaccination. Around, 78.30% female and male participants were unaware of the availability of HPV vaccination against cervical cancer. 90.06% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In one study, both male and female physicians were observed to be interested in recommending the HPV vaccine. 31 However, in this setting there was better perception among female PHC physicians. Although not assessed in this setting, the authors suspect that a limited disclosure of high risk sexual behavior between both male/female patients and PHC physicians of opposite gender might exist, given the conservative nature of this community and the sensitivity of discussing sexually transmitted diseases.…”
Section: Discussionmentioning
confidence: 88%
“…In one study, both male and female physicians were observed to be interested in recommending the HPV vaccine. 31 However, in this setting there was better perception among female PHC physicians. Although not assessed in this setting, the authors suspect that a limited disclosure of high risk sexual behavior between both male/female patients and PHC physicians of opposite gender might exist, given the conservative nature of this community and the sensitivity of discussing sexually transmitted diseases.…”
Section: Discussionmentioning
confidence: 88%
“…[ 30 ] Likewise, several studies in Saudi Arabia found unsatisfactory levels of knowledge pertaining to cervical cancer and screening. [ 3 24 25 26 27 30 31 32 33 34 ] All these results indicate the need for improvement in the levels of awareness about screening tools for cervical cancer. However, studies in Western countries showed better levels of knowledge of the Pap smear as a screening tool.…”
Section: Discussionmentioning
confidence: 99%
“…According to the study protocol, 84.8% of the participants showed poor total knowledge scores, similar to the findings of several studies in both developed and developing countries. [ 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 ] Thus, increasing the level of knowledge of cervical cancer in Saudi Arabia is important for the promotion of healthy behaviors and the use of preventive methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, cultural and religious beliefs, lack of access to healthcare facilities, and fear of side effects were also identified as major barriers. 7,12,13 To combat these barriers, it is critical to develop targeted interventions and awareness campaigns that are culturally and religiously sensitive. These campaigns must be relevant to women's specific needs.…”
Section: Discussionmentioning
confidence: 99%